HUBUNGAN ANTARA AGAMA DAN ILMU DALAM PANDANGAN AL FARABI - Tsuraya Syarif Zain (JIA (Jurnal Ilmu Agama), 2017)
Are religion and science in contradictory? This question is not easy to answer. In many ways, religion through the teachings of its Holy Scripture is different from the discovery of the sciences, for example the concept of creation is different from Darwin's theory of evolution. Starting from this problem the authors encourages to examine more deeply the relationship between science and religion related to the question of religious position for science and science for religion according to Al Farabi philosophical perspective. According to Al Farabi between Revelation as a source of religion and science are interwoved. So it can be concluded that in Islam there is integration between science and religion. Revelation comes from God, as well as other knowledge derived from the Absolute. Absolute knowledge is able to become a science because it benefits for human life and bring happiness for mankind. Such knowledge should then be deductible to be the principles of law with a strong principle of wisdom and prudence to make it a science